Analysis of fatigue failure in the rolling bearings - De Azevedo Silva, Fernando [UNESP]; Siqueira Guidi, Erick [UNESP] (SAE International, 2013)
The development of the technology of rolling bearings, such as cylindrical or thrust bearings has as one of its objectives constitute a set of mechanical components that combine mechanical strength and stiffness, designed to support the loads, speeds and life specified for a particular application. This project aims to discuss the application of the finite element method in the analysis of fatigue failure in rolling bearings, evaluating the influence of some construction and operational parameters in the stress distribution, such as geometry of contact surfaces, applied load, rotation, and properties of materials in contact. Specifically, we investigated the relationship between the stress caused by cyclic loading in fatigue life of these bearings. The analysis of the life of rolling bearings was performed using the commercial software ANSYS, based on the finite element method in a virtual environment. Expected that the results obtained in this study will be useful in developing methods for predicting fatigue failure in rolling bearings subjected to cyclic loads. © 2013 SAE INTERNATIONAL.